Impact of “The Blob” and “El Niño” in the SW Baja California Peninsula: Plankton and Environmental Variability of Bahia Magdalena - Jiménez-Quiroz, María del Carmen; Cervantes-Duarte, Rafael; Funes-Rodríguez, René; Barón-Campis, Sofía A.; García-Romero, Felipe de Jesús; Hernández-Trujillo, Sergio; Hernández-Becerril, David U.; González-Armas, Rogelio; Martell-Dubois, Raúl; Cerdeira-Estrada, Sergio; Fernández-Méndez, José I.; González-Ania, Luis V.; et al. (Frontiers in Marine Science, 2019)
Bahia Magdalena is a coastal lagoon with an enormous biological and fishing wealth; it is located in the Pacific coast of Baja California (Mexico), a transitional zone between tropical and temperate regions which is strongly affected by the global-scale climate phenomena. The objective of this work was to determine the impact of the unusual and consecutive warming events known as The Blob (TB2013–2015) and the 2015–2016 El Niño on the hydrological characteristics and plankton communities, the lower levels of the trophic web, from January 2015 to December 2017. This coastal lagoon lacks river runoff and primary producers depend on the upwelling’s nutrient supply. The environmental variables analyzed were the upwelling index (PFEL-NOAA), the air and sea temperature, salinity, nutrients, and chlorophyll-a. The species composition, species richness and the Shannon-Weiner diversity index were used to describe some aspects of the phytoplankton community structure and its phenology. The biomass and mortality of zooplankton also were analyzed. The seasonal pattern of hydrology was described with data collected in nine sampling stations. An alternative approach used with both biological and environmental datasets was to select representative sampling stations located in the vicinity of the inlet and in the interior of the lagoon. Chla-fluorescence imagery collected by the MODIS-Aqua satellite was used as an indicator of phytoplankton abundance. Statistical analyses included bi- and multivariate parametric and non-parametric tests. Principal component analysis was used to describe the seasonality of hydrological data and the canonical correlation analysis to relate environmental and biological datasets. The increase of temperature at a global and local scale in 2015 had as consequence an atypical increase in the water temperature in the fall of 2015, coincident with the abrupt diminishing of upwelling strength and input of nutrients advected from the ocean. A recovery of these two variables was recorded in 2016 at the end of the El Niño. The most abundant group of phytoplankton species were diatoms. Algal blooms were composed by species adapted to high temperatures and nutrients depletion in 2015, while in 2016 and 2017 were composed by ruderal-strategist species and they were boosted by the nutrient pulses associated with the spring upwellings. The fall algal bloom, typical of subtropical coastal lagoons, was observed only in 2016 and it was confined to the interior of the lagoon where there are local inputs of nutrients. In 2015 and 2016 there was a succession of diatoms and dinoflagellates related to the rising of temperature while in 2017 this pattern changed because of the strong upwellings. The relationships of water temperature and silicate with a ratio of diatoms’ cell abundance, was analyzed using generalized additive models (GAMs), showing significant correlations but different trends in some years. The species richness of diatom blooms was high; on the other hand, species diversity increased at the end of spring and early summer. The seasonal pattern of zooplankton biomass showed changes along the 3 years, but the most noticeable was an increase during winter and early spring 2015 and the lack of the usual high values of June–July in 2017. The seasonal pattern of the phytoplankton abundance was different in comparison with the 1982–1983 El Niño while the zooplankton was similar among the three strongest El Niño. The changes we observed strongly suggest that the warming caused by those phenomena highly affected the upwelling strength, the length of the temperate and warm seasons and the hydrology. Phenology of phytoplankton and zooplankton changed after the strong perturbation under the El Niño, and possibly The Blob. The recovery of phytoplankton biomass began in 2017, but its taxonomic composition was not adequate to support the zooplankton recovery.